Rainforest villages, eighteenth-century history. (October 2020) - Price, Richard
Based on long term ethnographic work with the Saamaka, and with the benefit of hindsight, this paper unpacks the specific ways in which the descendants of these Suriname Maroons have constructed and transmitted the historical knowledge of their 18th-century ancestors, who escaped slave plantations and confronted the colonial powers from their new settlements in the depth of the forest. In the process, they created an original memory of these historical events— First-Time or Fesiten knowledge—and managed to keep it alive. The article explores the specific ontology, frames and idioms of this historical knowledge, as well as its ideological role, the (dis)connections to hegemonic colonial memory devices, its evolution in time, the ways of transmission, and the memory specialists that have kept and circulated it.